Effects of aging on lateral stability in quiet stance - Nishihori, Takezumi; Aoki, Mitsuhiro; Jiang, Yifa; Nagasaki, Sachio; Furuta, Yoshinori; Ito, Yatsuji (Aging clinical and experimental research, 2012)
Background and aims: Recent studies have demonstrated that assuming the postural corrective torque is regulated by a proportional-integralderivative (PID) controller in the anterior/posterior direction, although few studies have discussed the medial/lateral (M/L) direction through PID control. Instability in the M/L direction has been reported to be closely related with the risk of falling in the elderly. The purpose of this study is to evaluate the mechanism of postural control in the M/L direction in the elderly. Methods: The movement of a marker on the subject’s back was measured by a CMOS video camera and trunk sway speeds in the M/L direction (TSSX) were calculated as absolute values in whole time series. Using trunk sway data, we identified the gain of PID parameters (proportional gain: K P , integral gain: K I derivative gain: K D ). In addition, we calculated the frequency spectrum of trunk sway using the marker locus from 0.016 to 5 Hz by fast Fourier transform. A total of 40 healthy subjects aged from 20 to 85 years old was evaluated with the PID control algorithm in a model of postural control in the M/L direction and their parameter values were estimated. Results: K P significantly increased with age, whereas K D tended to decrease. The TSSX and power ratio of medium frequency (0.2-2.0 Hz) significantly increased with age, but the power ratio of low frequency (0.02-0.2 Hz) tended to decrease. K P and K I were significantly correlated with the power ratio of medium frequency. There was a significant negative correlation between K D and TSSX. Conclusions: Our results indicate that dependence on hip and ankle stiffness, which may be controlled by proportional gain, increases with age for postural control in the M/L direction. A disability in the feedback mechanism based on velocity information for postural control, which may be associated with derivative gain, tends to increase with age but shows considerable individual variation.